A limit theorem for mixing processes subject to rarefaction. I - Gasanenko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We prove a limit theorem on the approximation of point mixing processes subject to rarefaction by general renewal processes. This theorem contains a weaker condition on the mixing coefficient than the known conditions.